2013
DOI: 10.1097/pec.0b013e31827b54c3
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Hypertonic Saline Use in the Pediatric Emergency Department

Abstract: Intravenous hypertonic saline use is increasing within the pediatric emergency department. Within this institution, it is most frequently used at a dosing range of 3 to 5 mL/kg and does not require central venous access for rapid infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…8,9 In a retrospective cross-sectional study, Brenkert et al 8 investigated administration of a bolus of 3% sodium chloride solution in 56 pediatric patients at an urban children's hospital, with 87% of doses administered via a peripheral catheter. No patient had indications of phlebitis or local tissue destruction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 In a retrospective cross-sectional study, Brenkert et al 8 investigated administration of a bolus of 3% sodium chloride solution in 56 pediatric patients at an urban children's hospital, with 87% of doses administered via a peripheral catheter. No patient had indications of phlebitis or local tissue destruction.…”
Section: Resultsmentioning
confidence: 99%
“…Tertiary references suggest administration via a largebore central catheter, although this recommendation is not based on actual safety evaluations in adult patients. 7 Peripheral intravenous administration of 3% sodium chloride solution has been studied in children, and results of a few studies 8,9 have indicated limited safety concerns. Proposed safety concerns associated with peripheral administration of a continuous intravenous infusion of 3% sodium chloride solution include extravasation, phlebitis, tissue ischemia, and venous thrombosis.…”
mentioning
confidence: 99%
“…Retrospective studies in the pediatrics population have found that patients who received these infusions peripherally had no evidence of adverse events. 15,16 A noteworthy limitation for these studies was the average durations of infusions under 1 hour, which may not be long enough to observe infusion-related adverse events (IRAEs).…”
Section: Introductionmentioning
confidence: 99%
“…Hypertonic saline (3% HTS) can be administered via a peripheral inserted catheter [6]. Modern evidence does not support the concern for HTS-induced intravascular hemolysis with peripheral vein administration in humans [7,8].…”
mentioning
confidence: 99%